(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
الايكورنيا نبات مائي استوائي أمريكي الأصل ينمو على سطح المياه العذبة، يُستخدم هذا النبات في معالجة الصرف الصحي، ويتم حالياً دراسة إمكانية استخدامه لمعالجة الصرف الصناعي، وذلك لتخفيض تراكيز المعادن الثقيلة. اُستُخدم النبات في هذه الدراسة لخفض تراكيز المعادن الثقيلة في المياه تم وفقها نمذجة التراكيز المصروفة من معامل البطاريات باستخدام نفس مجالات التراكيز و هي (100-300mgPb/l)، ( 15-50mgCd/l), (5-10mgMn/l)، وتم توزيع التراكيز وفقاً لتصميمResponse Surface لدراسة ثلاثة عوامل وهي تراكيز العناصر الثلاثة. استمرت التجربة لمدة 14 يوماً، تم خلالها دراسة التغيرات الحاصلة على قدرة تحمل النبات للتراكيز المختلفة من خلال متابعة التغيرات المرفولوجية التي ظهرت خلال هذه المدة بالترافق مع قياس تغيرات تراكيز العناصر الثقيلة في الوسط المائي، من خلال تحليل العناصر الثقيلة كل يومين خلال مدة التجربة. في نهاية التجربة جُمعت النباتات ،و تم تحديد نسب العناصر الثقيلة في كل من الجزء الهوائي (الخضري) والجزء المائي (الجذري). من خلال النتائج تم التوصل إلى أن النبات قادر على امتصاص العناصر الثقيلة من مياه الصرف الصناعي الملوثة بها، ولكن عند تراكيز محددة إلا أنه غير قادر على تحمل التراكيز العالية من العناصر الثقيلة(الرصاص والكادميوم والمنغنيز) مجتمعة. In this study Eichhornia crassipes was used under varying conditions of heavy metals concentrations, due to typical study for wastewater concentrations from the batteries factories, to decrease them. Moreover, the concentrations in different media of the plants have been distributed depending on the Response Surface design for three factors 100- 300mg Pb/l, 15-50mg Cd/l, 5-10mg Mn/l which are the concentrations of heavy metals in the wastewater of batteries factories. The experiment has continued for fourteen days in which a study has been made for the current changes over the plants endurance for the different concentrations by continuing the morphologic changes which have appeared through this period. The heavy metals concentrations of the media were measured during two days. At the end of the experiment, analyses for metals were also carried out on the plant samples to determine the effect of different media on metal accumulation by roots and aerial parts of the plants. The results showed that the plant can absorb heavy metals from the industrial wastewater which is polluted by them, but at certain concentrations. It is unable to survive in a mixture of high heavy metals concentrations of these three factors together(Pb, Cd, Mn).